Two new sesquiterpene dimers isolated from the roots of Saussurea lappa (Yunmuxiang). Issue 5 (4th May 2022) - Lai, Sheng-Tian; Zhang, Ting; Wang, Hong-Qing; Xie, Jun; Liu, Jian-Bo; Chen, Ruo-Yun; Kang, Jie
Abstract: Two new sesquiterpene dimers, lappadimers A and B, were isolated from the roots of Saussurea lappa (Yunmuxiang). Their structures were established on the basis of spectroscopic methods. They were found to have potential anti-inflammatory activity at 10  µ M and could reduce LPS-induced NO levels in murine macrophage, with inhibitory rates of 67% and 47%, respectively. Graphical Abstract: UF0001